The role of taxonomy in species conservation. - Mace, Georgina M (2004)
Taxonomy and species conservation are often assumed to be completely interdependent activities. However, a shortage of taxonomic information and skills, and confusion over where the limits to 'species' should be set, both cause problems for conservationists. There is no simple solution because species lists used for conservation planning (e.g. threatened species, species richness estimates, species covered by legislation) are often also used to determine which units should be the focus of conservation actions; this despite the fact that the two processes have such different goals and information needs. Species conservation needs two kinds of taxonomic solution: (i) a set of practical rules to standardize the species units included on lists; and (ii) an approach to the units chosen for conservation recovery planning which recognizes the dynamic nature of natural systems and the differences from the units in listing processes that result. These solutions are well within our grasp but require a new kind of collaboration among conservation biologists, taxonomists and legislators, as well as an increased resource of taxonomists with relevant and high-quality skills.